Penerapan E-Planning sebagai bentuk Sistem Perencanaan Daerah Berbasis Teknologi di Kabupaten Demak Tahun 2018 - 2019 - Maharani, Devita Dwi; Manar, Dzunuwanus Ghulam (Journal of Politic and Government Studies, 2020)
Government efforts in realizing Good Governance can be realized throughan integrated Electronic Government for Good Governance from the level ofregional government to the center. It is intended that the information andcommunication technology infrastructure that will be built can be utilizedmaximally to coordinate with all agencies, both at central and regional levels.The implementation of good governance in Demak Regency is realized throughthe application of E-Planning where in its application there are many obstaclesThe research method used is descriptive qualitative data collectiontechniques such as interviews and documentation. The data obtained were thenanalyzed using Triangulation Methods, Theory and Data Sources.The results of the research related to the implementation of e-planning inDemak Regency are the implementation of Regional Regulation No. 2 of 2018which is a follow-up of efforts to integrate the use of information technology ingovernment activities, especially those relating to development planning. Theimplementation process is modeling from a similar program in Batang District. Inthis case the E-Planning Application that is run is still in the web presence stagebecause when viewed in its application the E-Planning website does not provideinteractive space for the community. The process of initiation, provision ofinstruments, outreach and preparation has been carried out, but in itsimplementation there are still a number of problems including servers that areoften error with limited network capacity, over capacity access, causing operatorsto wait for a while to be able to log in, limited human resources qualified in thefield of programming, there are still many proposals that are not accommodatedproperly. However, with all the problems faced by the Demak Regencygovernment efforts so far it has been considered to be quite responsive in solvingproblems and both technical and non-technical obstacles encountered inimplementing E-Planning can be seen from 3 aspects including TechnologyAspect, when there is an error on the server, the response of the Demak Regencygovernment is quite fast only a few moments have been handled and the responseis fast. Then in the bureaucratic or technical aspects, When input is carried outwithin a scope of Bappeda, the Demak Regency Government increases thecapacity of the internet network at a certain time so that it is expected to minimizeerrors when input. Then when an urgent problem occurs but the Demak Regencygovernment cannot handle it by itself, the Demak Regency GovernmentÂ  coordinates with the Batang Regency to find solutions to the problems faced. In the aspect of Human Resources, Bappeda Litbang does not immediately release the operator independently but if there is a problem or the operator does not understand Bappeda continues to provide technical guidance in accordance with what is expected.Keywords: Good Governance, E-Government, Implementation